Biografías sexuales de los adolescentes varones en las favelas de Recife, Brasil: cuestionando algunos estereotipos de la sexualidad adolescente - Juárez, Fátima; Castro Martin, Teresa (El Colegio de México A.C., 2009)
This article analyzes adolescent sexual and contraceptive practices within the broader context of partnership dynamics, i.e. how frequently, with whom, for how long and under what conditions of commitment, exclusivity and sexual involvement, do adolescents establish partnerships. The data used were collected in a specially designed survey carried out in May 2000 among 1,438 adolescent males aged 13-19 in several favelas of Recife, Brazil. The survey collected detailed partnership, sexual and contraceptive histories in the form of month-by-month calendars for the two years prior to the interview. The results show that some features of adolescent partnership dynamics, such as short duration patterns, high prevalence of casual relationships, brief courtship before sexual involvement and limited contraceptive protection, enhance adolescents’ vulnerability to health risks. However, other features, such as sporadic dating, high prevalence of nonsexual partnerships, and hence relatively infrequent and intermittent sexual intercourse, limit their actual exposure to health risks, particularly in early and middle adolescence. Considerable continuity in contraceptive protection across successive partnerships is also found.